INDUSTRIAL ENGINEERING TECHNIQUES AND TOOLKIT ON BASIS OF COMMUNICATION PROCESS SCHEDULING - Tatyana V. Simonyan; Dmitry B. Dashchinskiy (Advanced Engineering Research)
Industrial engineering techniques are total operations and methods for the production or rendering services. The selection of the method and industrial engineering techniques — job shop-type, batch or repetitive — is primarily subject to the industrial scale. The manufacturing programme making, batch quantity and stock optimization depend on the size of the customer orders, and are determined by the diagnosis effectiveness. Production engineering processes are completed in the planning (including communication), forming the closed model of all productive processes of the enterprise.